2017
DOI: 10.1111/ijd.13460
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the clinical features of geographic tongue: unveiling its relationship with oral psoriasis

Abstract: GT is a symptomatic lesion with a thick halo. In contrast, psoriatic patients are frequently asymptomatic and exhibit severe lesions with greater loss of papillae that are associated with severe FT. The present study is the first to demonstrate clinical differences in the GT of patients with and without psoriasis, suggesting that some GT cases may represent true oral psoriasis and some cases may represent only GT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 39 publications
(70 reference statements)
0
42
1
8
Order By: Relevance
“…A few authors have queried whether this could be some local form of psoriasis. An investigation into the molecular mechanism of the disease has revealed that some cases of geographic tongue are caused by a mutation in the interleukin 36 receptor antagonist gene, which is also found in generalized pustular psoriasis . The interleukin 36 receptor antagonist gene encodes the interleukin 36 receptor antagonist, a soluble molecule that counteracts the inflammatory effect of interleukin 36 cytokines by binding their receptor, the interleukin 1 receptor L2, and preventing the downstream activation of nuclear factor kappa‐B signaling .…”
Section: Benign Migratory Glossitismentioning
confidence: 99%
“…A few authors have queried whether this could be some local form of psoriasis. An investigation into the molecular mechanism of the disease has revealed that some cases of geographic tongue are caused by a mutation in the interleukin 36 receptor antagonist gene, which is also found in generalized pustular psoriasis . The interleukin 36 receptor antagonist gene encodes the interleukin 36 receptor antagonist, a soluble molecule that counteracts the inflammatory effect of interleukin 36 cytokines by binding their receptor, the interleukin 1 receptor L2, and preventing the downstream activation of nuclear factor kappa‐B signaling .…”
Section: Benign Migratory Glossitismentioning
confidence: 99%
“…Most cases reported in the literature showed that concomitant tongue involvement, in the form of conventional geographic tongue, is very common (2,7). In contrast to GS, geographic tongue is very common and is characterized by the isolated tongue involvement (8). Patients affected by geographic tongue can be also affected by fissured tongue (3,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the etiology GT and FT is unknown, many authors tried to connect it with some systematic conditions and disease, as diabetes mellitus 7 , anemia, allergy 8,9 , celiac disease 10 , anxiety and emotional stress 11 etc. Although GT has been even defined as oral psoriasis 12 , lately some authors found difference in clinical appearance between GT at psoriatic and nonpsoriatic subjects 13 .…”
Section: Sample Collection and Cultivationmentioning
confidence: 99%